From Natural Compounds to Bioactive Molecules through NMR and In Silico Methodologies. Issue 40 (29th July 2020) - De Vita, Simona; Terracciano, Stefania; Bruno, Ines; Chini, Maria Giovanna
Abstract : Marine and terrestrial organisms are an unlimited source of active secondary metabolites. They are characterized by high chemical diversity, biochemical specificity, and other molecular features that make them a valid starting point for lead generation in the drug discovery process. Considering the complex structural architecture and the high number of stereogenic centers, compared to the synthetic drugs, the elucidation of the 2D structure and the assessment of the precise 3D arrangements of natural products (NPs) provide essential insights into ligand‐target interaction which can drive a rational lead optimization process. In this regard, the combination of NMR spectroscopy with modern computational techniques represents one of the most effective approaches to achieve this task. The DFT/NMR integrated method, and its application, in combination with the accurate ROE‐distance analysis, have been employed as valid support, both to clarify the configuration and conformational profile of the active secondary metabolites and to shed more light on the molecular basis of their mechanism of action. Indeed, the comprehension at a molecular level of their interactions with specific targets involved in pathologies, like inflammation and cancer, represents a cornerstone for further investigations through computational tools like molecular docking and molecular dynamics. These high‐efficiency in silico techniques play a crucial part in the drug discovery process as well as in lead optimization procedures. Furthermore, this integrated approach provides the identification of novel chemical platforms disclosing new bioactive molecules with enhanced potency and selectivity. Abstract : Natural products are a privileged class of compounds with high diversity which are suitable for inspiring new rationally designed multi‐target drugs. Herein, a multi‐disciplinary approach that covers the structural and pharmacological characterization of NPs for developing semisynthetic and synthetic derivatives with optimized potency/selectivity towards specific targets in the inflammatory/cancer field is proposed.